Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Thrifting (Survei pada Konsumen Pajak Melati di Kota Medan) - Sembiring, Tiffani Claudia Br.; Siregar, Dahrul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the influence of product quality and price perception on thrifting purchasing decisions among Pajak Melati consumers in Medan city. This study used a quantitative method with an associative approach, aiming to analyze the relationship between the independent and dependent variables. The sample size was 100 respondents, who were Pajak Melati consumers who had visited more than three times. This data was collected through a questionnaire and analyzed using SPSS version 25, using partial (t) tests, simultaneous (F) tests, and the coefficient of determination (R²) test. The results showed that the independent variables, product quality and price perception, each had a positive and significant effect on the dependent variable, purchase decisions. Both variables simultaneously also had a significant effect on purchase decisions. The adjusted R² value of 71.9% indicates that thrifting purchasing decisions among Pajak Melati consumers in Medan city ,can be explained by the influence of product quality and price perception, while the remaining 28.1% was influenced by other factors not examined in this study. The results of this study identified that the better the quality of thrifting products and their price perceptions, the more purchasing decisions of jasmine tax consumers in Medan City.